Mai de la Photo 1991. - Ville de Reims; Mai de la Photo 1991, Reims (Reims : Mai de la Photo, 1991)
Adilon, Blaise ; Adler, Gosbert ; Alberge, Bertrand ; Anorzejewska-Zieba, Ewa ; Barcik, Slawomir ; Berdyszak, Jan ; Berthélin, Catherine ; Bertoux, Quentin ; Bonfert, Gerd ; Bordier, Muriel ; Buchwald, Kurt ; Buignet, Christine ; Bulhak, Jan ; Drahos, Tom ; etc.
Mai de la Photo 1991, coproduction ville de Reims, du 16 mai au 9 juin 1991
boek